Circulation, déambulation et textes hétérogènes - Catherine Delarue-Breton; Jacques Crinon (Nantes Université, 2016)
In this study, we aim to highlight some ways in which students manage or fail to establish connections (between heterogeneous elements when reading composite - therefore non-linear - texts (Bautier et al., 2012), and when using multiple semiotic systems or verbal statements with various targets. In particular, we want to show that some students' are able to establish continuity between the various elements coming from these materials, while others find it more difficult. We also examine their ability to link various elements coming from these materials or other elements from their own experience. In this context, the teacher's role will be studied, especially the way he/she helps students make connections. We will analyse:the choice of material; the choice of educational devices (implementation, development); the arbitration during the students' verbal exchanges; the way each student's personal experience is taken into account.